2014
DOI: 10.1111/apt.12640
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: relief of upper gastrointestinal symptoms by an acid pocket‐targeting alginate–antacid (Gaviscon Double Action) – a double‐blind, placebo‐controlled, pilot study in gastro‐oesophageal reflux disease

Abstract: SUMMARY BackgroundThe alginate-antacid, Gaviscon Double Action (Gaviscon DA; Reckitt Benckiser, Slough, UK) suppresses reflux after meals by creating a gel-like barrier that caps and displaces the acid pocket distal to the oesophago-gastric junction. The effect of Gaviscon DA on reflux and dyspepsia symptoms has not yet been demonstrated with a modern trial design. AimA pilot study to assess the efficacy and safety of Gaviscon DA compared with matched placebo for decreasing upper gastrointestinal symptoms in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 38 publications
(59 reference statements)
4
40
0
5
Order By: Relevance
“…Among these, 35 were excluded for the following reasons: the study was not comparative, sodium was the active ingredient (one study), lack of quantitative data, or the study was not original or out of topic. Four studies finally met the inclusion criteria [11,17–19]. We found four additional records through other sources, including grey literature, by manual research [2023].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these, 35 were excluded for the following reasons: the study was not comparative, sodium was the active ingredient (one study), lack of quantitative data, or the study was not original or out of topic. Four studies finally met the inclusion criteria [11,17–19]. We found four additional records through other sources, including grey literature, by manual research [2023].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies were single-centre (6/8). The study design also varied, half were randomized controlled trials [19,21–23], three were uncontrolled before-after studies [17,18,20], and one was a nested case-control study [11]. Baseline cardiovascular and renal functions, and exclusion criteria are given in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Controlling heartburn in patients with NERD can also be achieved with antacid or alginate compounds. Many clinical trials have demonstrated the benefit of these drugs, which continue to have a role in quickly relieving typical reflux symptoms in both NERD and ERD . However, these over‐the‐counter drugs require multiple doses during the day because of their short duration of action.…”
Section: Medical and Surgical Treatment In Nerd He And Fhmentioning
confidence: 99%